2015
DOI: 10.1016/j.ecolecon.2015.01.006
|View full text |Cite
|
Sign up to set email alerts
|

What are shared and social values of ecosystems?

Abstract: Social valuation of ecosystem services and public policy alternatives is one of the greatest challenges facing ecological economists today. Frameworks for valuing nature increasingly include shared/social values as a distinct category of values. However, the nature of shared/social values, as well as their relationship to other values, has not yet been clearly established and empirical evidence about the importance of shared/social values for valuation of ecosystem services is lacking. To help address these th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
355
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 415 publications
(366 citation statements)
references
References 71 publications
3
355
0
8
Order By: Relevance
“…Building on past research that has distinguished among multilevel values (Klein and Kozlowski 2000, Manfredo et al 2014, Kenter et al 2015, we identified three categories that are relevant to the collective action situation in Ostrom's SESF: Cultural, Individual, and Assigned. First, Cultural values are guiding worldviews-or "ways of life"-that define a society (Inglehart et al 1998, Milton 2013.…”
Section: Multiple Levels Of the Value Conceptmentioning
confidence: 99%
See 2 more Smart Citations
“…Building on past research that has distinguished among multilevel values (Klein and Kozlowski 2000, Manfredo et al 2014, Kenter et al 2015, we identified three categories that are relevant to the collective action situation in Ostrom's SESF: Cultural, Individual, and Assigned. First, Cultural values are guiding worldviews-or "ways of life"-that define a society (Inglehart et al 1998, Milton 2013.…”
Section: Multiple Levels Of the Value Conceptmentioning
confidence: 99%
“…Moreover, our multilevel differentiation goes beyond the SESF's approach because it accommodates normative aspects of Assigned and Individual values (Irvine et al 2016), provides access to a body of literature that specifies scales of measurement and corresponding methods (van Riper and Kyle 2014), and introduces a group-level dynamic represented by Cultural values that is otherwise absent (Manfredo et al 2016). Moreover, scholarship that considers three levels of values provides a basis to conceptualize dynamics between collective action and changes in human preferences, particularly surrounding Assigned values that are deliberated and negotiated within stakeholder groups (Kenter et al 2015). Specifically, we assert that Cultural, Individual, and Assigned values are the foundation of inner views and expressed preferences that influence how natural resources are governed over time (Hoff-Elimari et al 2014).…”
Section: Multiple Levels Of the Value Conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent advances in the participatory literature also highlight the importance of participation to address complex and dynamic environmental problems [17], as well as the need to combine different approaches to capture different value dimensions [19][20][21][22]. From a similar standpoint, the field of "deliberative ecological economics" advocates for deliberative valuations to improve the quality of sustainable decision-making because deliberative processes are assumed to be more legitimate, fair and democratic [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Ecosystem service (ES) assessments have traditionally focused on identifying the individual monetary values for each ecosystem service [12,13]. However, the lack of theoretical frameworks has led to subjective judgments and criticisms [14][15][16]. The integration of deliberate and non-monetary valuation approaches to ES valuations has increasingly been advocated as a way of revealing the wider value concepts.…”
Section: Introductionmentioning
confidence: 99%